Library Services in Improving Private Islamic Institutes Students' Reading Interest - Suhairi Suhairi; Adrianus Chatib; Minnah El Widdah (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze library services at each private Islamic religious institute in Jambi Province. The focus of the discussion in this study is the implications of library services in increasing student interest in reading. The type of this research is the category of qualitative research with descriptive analytical study method. Data collection was carried out using observation, interview, and documentation techniques. Furthermore, the data were analyzed using reduction techniques, data presentation, and drawing conclusions. Finally, the data is declared valid/valid if it has gone through data triangulation. The results of this study indicate that the management of library services in increasing the reading interest of private IAI students in Jambi Province has not been carried out properly. Thus, it affects students' reading interest. This is due to several inhibiting factors, namely: library facilities that have not been maximized, operational costs are still minimal, managers or human resources are still low, low motivation from within the students themselves, and their busyness in activities outside campus.